Access, awareness, and risk: drivers of unsafe sharps disposal and needle reuse in insulin-treated adults in China - Wu, Shaoping; Wang, Fang (Frontiers in Public Health, 2025)
BackgroundUnsafe household sharps disposal and needle reuse among insulin-treated adults pose clinical and public health risks; however, population-based data from China are limited.MethodsWe conducted a cross-sectional survey of consecutive insulin-treated outpatients at a tertiary hospital in Enshi, Hubei (February 2023–December 2024). A cross-culturally adapted questionnaire captured 30-day disposal and reuse practices, community-safety incidents, and access determinants. Primary outcomes were unsafe disposal (household trash, public bins, or toilets/sinks) and any needle reuse. Multivariable logistic regression estimated adjusted odds ratios (aORs) with 95% confidence intervals (CIs).ResultsAmong 1,810 insulin-treated adults, unsafe sharps disposal was widespread (59.0%; 95% CI: 56.7–61.2%). Disposal methods included loose trash at 43.5%, public bins at 15.9%, and approved containers at 24.7%. Needle reuse was reported by 32.5% (95% CI: 30.4–34.7%); among reusers (n = 588), the primary reason was cost (47.1%). In adjusted models, unsafe disposal was associated with younger age (<30 years, aOR: 2.31; 95% CI: 1.42–3.76; 30–44 years: aOR: 1.67; 95% CI: 1.28–2.18), male sex (aOR: 1.38; 95% CI: 1.14–1.67), lower education attainment (no formal/primary education: aOR: 2.84; 95% CI: 2.02–3.99), low income (aOR: 3.42; 95% CI: 2.31–5.07), travel time >30 min (aOR: 1.94; 95% CI: 1.51–2.49), lack of awareness about take-back programs (aOR: 2.12; 1.75–2.57), and limited availability of containers (aOR: 2.45; 95% CI: 2.01–2.98), pump usage (aOR: 0.45; 95% CI: 0.27–0.75), and counseling (aOR: 0.35; 95% CI: 0.29–0.43). Needle reuse showed similar patterns: younger age (aOR: 1.89; 95% CI: 1.18–3.03), male sex (aOR: 1.29; 95% CI: 1.07–1.55), lower education (aOR: 2.16; 95% CI: 1.56–2.99), low income (aOR: 2.87; 95% CI: 1.95–4.24), diabetes duration ≥10 years (aOR: 1.34; 95% CI: 1.11–1.61), travel time >30 min (aOR: 1.78; 95% CI: 1.39–2.28), lack of awareness (aOR: 1.87; 95% CI: 1.55–2.26), limited availability of containers (aOR: 3.21; 95% CI: 2.64–3.90), pump usage (aOR: 0.31; 95% CI: 0.15–0.64), and counseling (aOR: 0.42; 95% CI: 0.35–0.51). Community safety risks increased: unsafe disposal raised the odds of household needlestick (aOR: 3.47; 95% CI: 2.01–5.99) and observed the presence of needles in the community (aOR: 2.89; 95% CI: 1.85–4.52). Additionally, the reuse of needles has also increased, impacting both household needlestick incidents and community needle observations (aOR: 2.23; 95% CI: 1.42–3.50; aOR: 1.67; 95% CI: 1.13–2.47).ConclusionUnsafe disposal and needle reuse are prevalent and exhibit strong socioeconomic gradients. Targeted education, container provision, and accessible take-back programs may improve patient and community safety in China.